In Vivo Study of Inoculation Approaches and Pathogenicity in African Swine Fever - Qian Xu; Dongfan Li; Xiaoyu Chen; Xiaoli Liu; Hua Cao; Hui Wang; Haowei Wu; Tangyu Cheng; Wenhui Ren; Fengqin Xu; Qigai He; Xuexiang Yu; et al. (Veterinary Sciences)
African swine fever is an extremely infectious viral disease that can cause nearly 100% mortality in domestic pigs. In this study, we isolated an ASFV strain HB31A and characterized it using hemadsorption assay, immunofluorescence assay, and electron microscopy. We then performed animal experiments on 20-day-old pigs through intramuscular and oronasal inoculations with HB31A. Pigs in the intramuscular group exhibited more consistent clinical disease, with an incubation period of 4.33 ± 0.47 days and a 100% mortality rate within 6.67 (±0.47) days post-inoculation (dpi). In contrast, the oronasal group experienced a longer course of disease, with an incubation period of 6.00 ± 0.82 days. Two out of three pigs in the oronasal group died at 8 and 10 dpi, while the surviving pig exhibited chronic disease and persistent infection, intermittently excreting ASFV through the oral, nasal, and rectal pathways. Virus DNA was found in oral, nasal, and rectal swabs at 1–3 dpi in the intramuscular group and at 3–5 dpi in the oronasal group. In summary, HB31A is highly lethal to domestic pigs, and field-infected pigs have the potential to develop non-lethal, chronic disease and persistent infection, with intermittent viral shedding, even when infected with a highly virulent strain. These findings offer a valuable understanding of the viral dynamics and pathogenicity of ASFV and highlight the difficulties in diagnosing, preventing, and controlling African swine fever.